Effects of the Menstrual Cycle and Mitigating Its Impact in Resistance-Trained Women - SantaBarbara, Kimberly (Auckland University of Technology, 2023)
Women’s participation in exercise and sport has increased, yet there is less research on female exercisers than males. The primary physiological difference between males and females is the MC, which is the regular hormonal cycle in reproductive-age women marked by sex hormone changes of up to 100% in a single day. MC symptoms affect over 90% of females, and the literature suggests that MC hormonal changes may affect RT performance. However, many direct studies observe no apparent effect on performance attributable to specific MC hormones. Therefore, this thesis aimed to add to the limited literature on normative MC characteristics in RT females to elucidate how the MC affects their performance and to investigate a novel method to reduce MC symptoms. First, RT females were surveyed regarding their MC to determine its characteristics, assess the prevalence of MC symptoms, and uncover its perceived effects on RT performance. In the 809 respondents, MC symptoms were highly prevalent (92%) and most (59%) perceived that their MC negatively affected performance. Further analysis examined the relationship between diet, body image, and eating disorders among RT women. Mental health appears to be impacted by the MC, and is an important consideration for RT women that should be openly discussed and addressed in sport settings. Building on this survey data with objective methods, a monitoring study was conducted measuring MC characteristics and symptoms in conjunction with well-being and perceived performance in a cohort of RT females for three MCs. Notably, there was a high prevalence of cycle irregularity, and inter- and intra-individual variation in the MC within this cohort. Further, there were distinct temporal patterns, such as a significantly higher probability of poorer mental health during the beginning and end of the MC, lower estimated one-repetition maximums at the end of the MC, and lower perceived recovery status scores at both the beginning and end of the MC. These data demonstrate the importance of accounting for inter- and intra-individual MC variation cycle-to-cycle, the commonality of irregular cycles, and patterns of MC symptoms in RT women. Having established the commonality of physiological and psychological MC-related symptoms in RT women, the final study investigated the influence of a mindfulness-based yoga protocol on MC symptoms, measures of well-being, and performance in a cohort of RT women. In a crossover design, RT women engaged in a daily at-home yoga practice for one MC. The yoga intervention was significantly associated with lower levels of bloating, low back pain, menstrual cramps, and stress. Furthermore, perceived performance was significantly more stable across the MC when daily at-home yoga was performed. Daily, at-home, mindfulness-based yoga may reduce MC symptoms in RT women and warrants consideration and further study. Further research should investigate the array of MC experiences, how mental health effects are associated with the MC, and establish additional methods for effectively reducing MC symptoms in athletic populations. Based on the findings within this thesis, MC concerns should be treated with an individualised approach due to the considerable amount of individual variability.